2007
DOI: 10.1677/joe-07-0501
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of mammary parenchymal growth by the fat pad in prepubertal dairy heifers: role of inflammation-related proteins

Abstract: In prepubertal heifers, the mammary parenchyma consists of epithelial and myoepithelial cells growing within a mammary fat pad (MFP). The MFP produces IGF-I that stimulates epithelial cell proliferation. In other species, adipose tissue expansion induces inflammation-related proteins (IRP), such as tumor necrosis factor a (TNFa), interleukin (IL)-6, IL-1b transforming growth factor b, monocyte chemoattractant protein 1 (MCP-1), and plasminogen activator inhibitor-1 (PAI-1). The MFP production of IRP may influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(56 reference statements)
1
15
0
Order By: Relevance
“…On the other hand, little is known about the suitability of tissue fragments from heifers in establishing primary cell cultures. Mammary epithelial cell cultures, especially organoids from heifer tissues, were analyzed in the past rather to examine the mitotic effects of cell proliferation (Berry et al 2003; Thorn et al 2008). In the current study, a very low level of CSN2 gene expression was detected in cultures obtained from all samples (heifers, lactation, and involution).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, little is known about the suitability of tissue fragments from heifers in establishing primary cell cultures. Mammary epithelial cell cultures, especially organoids from heifer tissues, were analyzed in the past rather to examine the mitotic effects of cell proliferation (Berry et al 2003; Thorn et al 2008). In the current study, a very low level of CSN2 gene expression was detected in cultures obtained from all samples (heifers, lactation, and involution).…”
Section: Discussionmentioning
confidence: 99%
“…The parenchyma is the portion of the mammary gland (udder) that is considered to be the functional aspect of the gland as this region contains the mammary epithelial cells (MECs) 32. MECs, responsible for producing milk, are the focus of the majority of research pertaining to mammary gland in cattle.…”
Section: Structural and Functional Anatomy Of The Bovine Mammary Glandmentioning
confidence: 99%
“…The responses to these proteins were also measured in MAC-T cells at Cornell University (Thorn et al, 2008), and the results showed that the responses in MAC-T cells were very similar to primary mammary epithelial cells.…”
Section: Cell-based Models Of the Mammary Glandmentioning
confidence: 99%
“…In a recent study, primary mammary cells were also used as a model system in which responses to inflammation-related proteins TNF-a, IL-1b and IL-6, MCP-1 and PAI-1 were measured (Thorn et al, 2008). The responses to these proteins were also measured in MAC-T cells at Cornell University (Thorn et al, 2008), and the results showed that the responses in MAC-T cells were very similar to primary mammary epithelial cells.…”
Section: Cell-based Models Of the Mammary Glandmentioning
confidence: 99%